HISTOPATHOLOGICAL STUDY OF THE MIDDLE EAR MUCOSA IN OTITIS MEDIA WITH EFFUSION IN CHILDREN - Kaneko, Yukie; Kikuchi, Yasutaka; Esaki, Shiro; Aoki, Kazuhiro; Moriyama, Hiroshi (JIBI INKOKA TEMBO, 1993)
Otitis media with effusion (OME) is caused by inflammation of the epipharynx, eustachian tubal dysfunction and discharge into the mastoid cavity. These process is associated with the change in the middle ear mucosa. We performed histopathological study on the middle ear mucosa in OME in children, and also investigated the relation to the mastoid pneumatization and to adenoids. The subjects consisted of 27 cases or 34 sides of OME in children aged from 4 years to 14 years. Middle ear mucosal samples were taken during adenoidectomy and insertion of middle ear ventilation tube under general anesthesia. Before tube insertion, we did myringotomy and carried out biopsy. We studied the epithelium and the subepithlial layer of the middle ear mucosa and classified them into 4 categories. On the result, severe subepithelial layer changes were observed in 53% of the cases in poorly pneumatized mastoid cell group. On the other hand, these changes were observed in 17% of the cases in the well pneumatized mastoid cell group. Adenoid changes were observed in 71% of cases with OME in children. Adenoid appeared to play an important role in the etigology of OME.